Dynamics model of NIMBY risk diffusion system in 'The Belt and Road' energy investment. (August 2020) - Sun, Jin-Hua; Hu, Jia-Li; Pu, Dong; Hu, Jian
Abstract: Through the analysis of the interaction among various influencing factors in the 'NIMBY' risk diffusion system, the boundary of NIMBY risk diffusion system in 'The Belt and Road' energy investment is determined, and the basic assumptions of the system dynamics model are made. On this basis, a causal relationship diagram of NIMBY risk diffusion is established, and the mechanism of nimby risk diffusion is explained in the form of cause tree. Moreover, based on the causal relationship diagram, the flow diagram of NIMBY risk diffusion system was established, and the system dynamics model framework was determined.